Flypaper Effect on Operating Expenditure and Capital Expenditure of the City Government in Indonesia - Purbarini, Endah; Masdjojo, Gregorius N. (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
This research analyze the possibility of flypaper effect on Operating Expenditure (OE) and Capital Expenditure (CE) of the City Government in Indonesia. The research also tested the effect of the Original Regional Revenue (ORR) and the General Allocation Fund (GAF) against OE and CE in the period of 2010-2012. Types of data used was the data panel, which is a combination data 2010-2012 time series and cross section 56 city. This research used panel data regression analysis which is estimated by Fixed Effect Model (FEM) and Random Effect Model (REM). The results of this research indicate that the ORR and GAF have positive and significant effect on OE. Furthermore this research find that flypaper effect occurs in OE. But the GAF is not significant to the CE. The ORR have a positive and significant effect on CE. Furthermore this research find that flypaper effect does not occur on CE.